Biomechanical origins of osteoporosis - McNamara, Laoise Maria (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2004)
The contention of this thesis is that a pathological change in bone tissue material properties during osteoporosis ahers the mechanical stimuli to bone remodelling cells and drives them to adapt the trabecular architecture resulting in a reduction in bone strength. To argue the case for this thesis, three separate but inter-related hypotheses with respect to the regulatory mechanisms governing bone remodelling are tested. These hypotheses are (1) A pathological change in the material properties of bone tissue occurs during osteoporosis, (2) Bone remodelling is regulated by a combination of strain and damage, and (3) Suppressing bone turnover in drug treated bone results in weaker bone tissue than that of normal and osteoporotic bone.
Keywords: Biomechanical Engineering, Ph.D.; Ph.D. Trinity College Dublin